INDEXED ASSESSMENT OF PERIODONTAL TISSUE IN PATIENTS WITH EARLY FORMS OF GENERALIZED PERIODONTITIS ON A BACKGROUND OF DIABETES TYPE I DIABETIC CARDIOMYOPATHY - R. Shkrebnyuk (Український стоматологічний альманах, 2018)
Patients with initial signs of generalized periodontitis on a background of diabetes type I diabetic cardiomyopathy and in healthy individuals with generalized periodontitis original - the first degree, for the study of periodontal tissue were determined in comparative perspective periodontal indexes (PMA, PI index bleeding gums, depth of periodontal pockets, tooth mobility, Rtg-index bleeding, loss of epithelial attachment). Proved that the index data estimates in generalized periodontitis patients with early forms of the disease against a background of diabetes type I on the background of diabetic cardiomyopathy prove more intense inflammatory and destructive changes in zuboutrymuyuchyh tissues compared with similar values in healthy individuals.